Study of the Causes of Discharge against Medical Advice in a Hospital of Shiraz University of Medical Sciences - Tahereh Shafaghat; Mohammad Kazem Rahimi Zarchi; Zahra Kavosi; Ali Ayoubian (Tehran University of Medical Sciences, 2017)
Background and Aim: The number of patients who leave hospital against medical advice could reflect patient dissatisfaction and it is a notable important problem. The present study aimed to identify the causes of discharge against medical advice at a hospital of Shiraz University of medical sciences. Materials and Methods: This was a qualitative study using grounded theory. Data were collected through telephone interviews with patients or their concomitants. All interviews were recorded by researcher and thematic method used to analyze the data. Based on it, causes of discharge against medical advice were determined and solutions were provided. Results: Causes of discharge against medical advice were categorized into 3 general themes: "causes related to the status of the hospital", "causes related to hospital staff", and "causes related to patients" that each of them include some sub-themes. Between the sub-themes, the issues relating to the hospital staff and economic status of patient had the most and the least frequency respectively. Conclusion: The research findings make it possible for the hospital managers to find solutions to prevent creation of DAMAs and side effects for early discharged patients, patientschr('39') readmission and imposing additional costs on them. These solutions can be mentioned as attention and understanding of authorities, preparing some amenities for patients, holding justification meetings for medical personnel and students and reengineering some hospital processes.